One nation, uninsured why the U.S. has no national health insurance - Quadagno, Jill S. (New York ; Oxford : Oxford University Press, 2005)
Every industrial nation in the world guarantees their citizens access to essential health care services - every country, that is, except the United States. Indeed, one in eight Americans - a shocking 43 million people - the majority in working families, do not have any health care insurance. This title offers a history of America's failed efforts to address the health care needs of its citizens.
Description based on print version record.
Includes bibliographical references.
Keywords: National health insurance -- United States -- History -- 20th century; Medically uninsured persons -- United States -- History -- 20th century; Health insurance -- Government policy -- United States -- History -- 20th century; Right to health -- United States -- History -- 20th century; Health services accessibility -- United States -- History -- 20th century; Health care reform -- United States -- History -- 20th century; Medical policy -- United States -- History -- 20th century